2015
DOI: 10.3390/molecules201219810
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reactivity of Na[W2(μ-Cl)3Cl4(THF)2]∙(THF)3 towards the Polymerization of Selected Cycloolefins

Abstract: Abstract:The bimetallic compound Na 3 Cl 4 (THF) 2 ]¨(THF) 3 (1, {W 3 W} 6+ , a 12 e 14 ) is a highly efficient room-temperature initiator for ring opening metathesis polymerization (ROMP) of norbornene (NBE) and some of its derivatives. In most cases, addition of phenylacetylene (PA) as co-initiator improves the catalytic activity and retains the high cis-stereoselectivity. On the other hand, 1 can polymerize cyclopentadiene (CPD), not via a metathetic, but rather, via a cationic mechanism. Here, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The 1 H NMR spectrum of PVNBE ( Figure S9) could not provide information about the configuration of the polymer, because signals of olefinic protons of the polymeric chain overlap with the vinylic ones, but indicated that the ring-strained C=C bond was cleaved, while the vinylic one was left intact and available for functionalization [23]. The same reactivity was observed with 2 [19] and 2/PA [20] and is rather unusual. The pendant vinyl group is usually involved in metathesis reactions, leading to cross-linked products; therefore, that monomer is used for the synthesis of self-healing polymers [24].…”
Section: Polymerization Reactionsmentioning
confidence: 66%
See 4 more Smart Citations
“…The 1 H NMR spectrum of PVNBE ( Figure S9) could not provide information about the configuration of the polymer, because signals of olefinic protons of the polymeric chain overlap with the vinylic ones, but indicated that the ring-strained C=C bond was cleaved, while the vinylic one was left intact and available for functionalization [23]. The same reactivity was observed with 2 [19] and 2/PA [20] and is rather unusual. The pendant vinyl group is usually involved in metathesis reactions, leading to cross-linked products; therefore, that monomer is used for the synthesis of self-healing polymers [24].…”
Section: Polymerization Reactionsmentioning
confidence: 66%
“…In addition, it showed similar reactivity with 2/PA towards the ROMP of DCPD [20], which seems to be the least reactive of the monomers studied, as long reaction times were required with either system.…”
Section: Polymerization Reactionsmentioning
confidence: 78%
See 3 more Smart Citations